Teaching first and second conditionals through comprehensible input in secondary school (based on Stephen Krashen's Input Hypothesis) - Єрмак, Карина; Стафеєва, Дарина (Київський національний університет імені Тараса Шевченка, 2025)
The publication presents a methodological lesson scenario for teaching English grammar to 10th-grade secondary school students based on Stephen Krashen's Input Hypothesis. The proposed lesson focuses on developing learners' understanding and practical use of the First and Second Conditional structures through comprehensible input and low-anxiety learning environments. The lesson integrates several stages: emotional warm-up activities to lower the affective filter; meaning-focused listening tasks; guided noticing of target structures; explicit clarification of grammatical patterns; and communicative pair work to promote spontaneous language production. The tasks provide students with opportunities to perceive grammatical structures in meaningful contexts, compare real and hypothetical situations, and incorporate conditionals into speaking activities. Special emphasis is placed on the transition from implicit acquisition to explicit knowledge through guided discovery and structured exercises. The communicative output stage encourages learners to produce their own sentences and engage in creative and situational discussion, fostering both fluency and grammatical accuracy. The proposed methodology is expected to support more natural acquisition of grammar through comprehensible input, while interactive tasks are designed to enhance students' motivation, creativity, and confidence in communication. The structure of the lesson integrates cognitive, communicative, and social competencies, making it a methodologically suitable model for contemporary secondary school environments.

У публікації наведено план уроку з навчання англійської граматики учнів 10-го класу закладів загальної середньої освіти на основі вхідної гіпотези Стівена Крашена. Запропонований урок зосереджений на розвитку розуміння учнів та практичного використання структур First and Second Conditionals через зрозумілий вхідний матеріал та навчальне середовище з низьким рівнем тривожності. Урок інтегрує кілька етапів: вправи для зниження афективного фільтра; завдання на аудіювання, орієнтовані на зміст; кероване засвоєння цільових структур; експліцитне пояснення граматичних моделей; та комунікативну парну роботу для стимулювання спонтанного мовлення. Завдання надають учням можливості сприймати граматичні структури в змістовних контекстах, порівнювати реальні та гіпотетичні ситуації та впроваджувати умовні речення в мовленнєві вправи. Особливий наголос зроблено на переході від імпліцитного засвоєння до експліцитного знання через керовані та структуровані вправи. Етап комунікативного продукування заохочує учнів створювати власні речення та брати участь у творчих і ситуативних обговореннях. Запропонована методика сприяє природніше засвоєння граматики через зрозумілий вхідний матеріал, тоді як інтерактивні завдання спрямовані на підвищення мотивації, креативності та впевненості учнів у спілкуванні. Структура уроку інтегрує когнітивні, комунікативні та соціальні компетентності, що робить його методично відповідним для сучасних закладів загальної середньої освіти.
Урок з англійської мови для 10 класу середньої школи (рівень стандарту) з теми "First and second conditionals through comprehensible input" (на основі гіпотези мовного введення Стівена Крашена)
Keywords: First Conditional; Second Conditional; comprehensible input; affective filter; acquisition; Stephen Krashen; secondary school; grammar teaching; communicative approach; First Conditional; Second Conditional; зрозумілий вхідний матеріал; афективний фільтр; засвоєння; Стівен Крашен; заклад загальної середньої освіти; навчання граматики; комунікативний підхід